Peran Mediasi Perceived Value dalam Memediasi Pengaruh Experiental Marketing terhadap Behavioral Intention (Studi pada Wisata Wahana di Kota Batu) - Mohammad Fakhruddin Mudzakkir; Iva Nurdiana Nurfarida (Trunojoyo University of Madura, 2018)
The purpose of this study is to find out the role of perceived value in mediating experiential marketing influence towards Behavioral Intention of visitors in Wisata Wahana of Batu City. The samples were 100 respondents from visitors of Eco Green Park, Jatim Park I and II. analysis technique using path analysis. The result of the study shows that experiential marketing has significant and positive influence towards perceived value and Behavioral Intention. The perceived value variable has been proven to be able to mediate experiential marketing influence towards the Behavioral Intention of visitors significantly, while the mediation happen is partial, because without the perceived value variable as mediation, the experiential marketing variable can affect the Behavioral Intention.